2022
DOI: 10.3389/feart.2022.985740
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of siderite and its implication for high conductivity anomaly in the slab-mantle wedge interface

Abstract: Carbonate minerals as a dominant carbon host can be transported to the Earth’s deep interior via subduction of the oceanic lithosphere, and their physicochemical behavior potentially has a significant influence on the compositional heterogeneity and physical properties in the deep mantle. In this study, we measured the electrical conductivity of natural siderite at 1–3 GPa and 100–700°C using a complex impedance analyzer in a large volume multi-anvil high-pressure apparatus. A sharp increase in conductivity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Generally, the conductivity becomes higher with increasing pressure when the small polaron hopping conduction mechanism is dominant as is the case with ferropericlase (Yoshino et al 2011;Liu et al 2014;Zhao et al 2020). This might be why the electrical conductivity of siderite is higher than that of siderite previously measurements at 1-3 GPa at 373 K (Hu et al 2022) as shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Generally, the conductivity becomes higher with increasing pressure when the small polaron hopping conduction mechanism is dominant as is the case with ferropericlase (Yoshino et al 2011;Liu et al 2014;Zhao et al 2020). This might be why the electrical conductivity of siderite is higher than that of siderite previously measurements at 1-3 GPa at 373 K (Hu et al 2022) as shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 59%
“…At low temperatures, the small polaron (electron-hole hopping between Fe 2+ and Fe 3+ ions) is likely to be the predominant conduction mechanism in siderite with the characteristic of a relatively lower activation energy (Hu et al 2022). Generally, the conductivity becomes higher with increasing pressure when the small polaron hopping conduction mechanism is dominant as is the case with ferropericlase (Yoshino et al 2011;Liu et al 2014;Zhao et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation